Cellulose nanofiber reinforced curcumin-infused calcium phosphate silicate cement for various bone-tissue engineering application - Lu, Xiu Guo; Meng, Sha Li; Zhou, Qiu Jing; Wu, Tao; Gong, Xing Tian; Wu, Qiong (Frontiers in Oncology, 2025)
IntroductionThis study utilized a injectable curcumin (Cur)-infused calcium phosphate silicate cement (CPSC) for addressing defects caused by bone cancer, and evaluated its promoting bone regeneration and exerting cytotoxic effects on osteosarcoma cells.MethodsThe material’s physicochemical properties, biocompatibility with osteoblasts, and cytotoxicity toward osteosarcoma cells were rigorously analyzed.ResultsThe findings demonstrate that CPSC-Cur signicantly prolongs the setting time, which can be optimized by adding silanized cellulose nanober (CNF-SH) to achieve a balance between workability and mechanical strength. Biological assessments reveal a pronounced cytotoxic effect on osteosarcoma cells while maintaining minimal toxicity toward pre-osteoblasts, highlighting CPSC-Cur’s potential as a promising material for repairing bone defects following cancer removal.ConclusionThis study lays the groundwork for future investigations into CPSC-Cur’s in vivo efficacy and its role in the clinical treatment of bone cancer.